Defining the Building Blocks and the Priority Areas for Cooperation Under the Belt and Road Initiative (International Journal of Built Environment and Sustainability, 2021)
The Belt and Road Initiative (BRI) is a China’s endeavour to globally connect the countries along two major routes. This paper examines the keywords defining the building blocks and priority areas under the BRI and their relationship in order to foster a practical understanding of the BRI for enhancing regional cooperation and connectivity along the routes. The methodology employed was a systematic literature review involving four stages. Firstly, a broad search in the Scopus database (2016-2020) using BRI or similar terms returned n=1,710 articles which were further limited using the keywords: building blocks, priority areas, policy coordination, infrastructure connectivity, unimpeded trade, financial integration and people-to-people exchange. Other keywords considered were community and Silk Road. The articles were then screened and assessed resulting in 155 articles reviewed in this study. The review reveals that while the building blocks are the aim motivating the BRI, hence the spirit behind it, the five priority areas provide practical methods through which China and other countries along the Belt and Road routes will focus their collective development. The relationship between the two aspects owes to the fact that people are involved at all spheres of the initiative bringing about emphasis on the people-to-people exchange which is a core part of social dimension in sustainable development. In contribution, this paper presents a unique perspective for looking at the BRI for a focused discussion of its cooperative framework which could serve as a foundation for further research in various sectors
Keywords: Belt and Road Initiative; Green Development; Peace; Regional Cooperation and Connectivity; Shared Global Community; Silk Road